Series of Activities ‘Gebyar Remaja Kampung KB’ Panggung Village Kota Tegal - Siti Sundari; Delia Jayanti Wulandari; M Sofyan Febriyanto (ASEAN Journal of Empowering Community, 2021)
We use “Gebyar Remaja Kampung KB” The reason and purpose are base on observations and interviews with one of the doctors at Panggung Health Center, dr. Luluk discussed with KKN students who agreed to carry out a coaching work program for the youth of the village stage by holding a “Gebyar Remaja Kampung KB” held for four days. Training activities “Gebyar Remaja Kampung KB” is essential because it is helpful to increase knowledge or skills, especially for those who prepare for the “Gebyar Remaja Kampung KB” event. Therefore the purpose of holding Training is as follows: (1) increase the creativity of the youth to display something new, (2) improve morale and behavior so that the youth remain polite and polite, (3) reduce the possibility of mistakes during the event, (4) give participants a platform to develop the potential that they have been having, (5) develop the creativity of the participants in the field of Gebyar Remaja and (6) grow and develop the confidence of the participants Gebyar Remaja.